Percentage analysis of scientific productivity of speech, language & hearing science professors at USP - Herculano, Rondinelli D.; Norberto, Ana Maria Q. (Medicina (Ribeirao Preto), 2009)
The University of São Paulo has three undergraduate courses of speech-language and hearing science offer by Faculty of Medicine (FM), Faculty of Odontology of Bauru (FOB) and Faculty of Medicine of Ribeirão Preto (FMRP). Using data retrieved from the Lattes Plataform database (Curriculum Lattes) we have quantitatively the scientific productivity percentage of speech, language & hearing science professors at USP. We observed that bibliometric evaluations using the Curriculum Lattes (CL) showed that the professors published papers in journal are not indexed by ISI. We showed that speech-language and hearing science professors at USP concentrated his paper in few journals (Brazilian Journal of Speech, Language & Hearing, CEFAC, Pró-Fono, Journal of Brazilian Society of Speech, Language and Hearing Science and Brazilian Journal of Otorhinolaryngology).